The forming system simulation for reactive gas ion source with decreased neutral gas inleakage - Martynenko, P.A. (Вопросы атомной науки и техники, 2017)
This report is devoted to research of possibility of acceleration N ions with original system of ions extraction and acceleration. The simulations of its electrode geometry for nitrogen ions acceleration are described. The parameters of its optimization for nitrogen ions acceleration are described. Comparison of the simulation results with the experimental dates was done.